One Fluorophore‐Two Sensing Films: Hydrogen‐Bond Directed Formation of a Quadruple Perylene Bisimide Stack. Issue 59 (22nd August 2022) - Gou, Xinyu; Wang, Zhaolong; Shi, Qiyuan; Liu, Ke; Jiang, Qingwei; Lin, Simin; Miao, Rong; Fang, Yu
Abstract: Elaborately designed π‐stacked molecular aggregates are significant for modulation of photophysical properties of polycyclic aromatic hydrocarbons (PAHs). Herein, a double hydrogen‐bonds trussed di(pyridyl)pyrrole‐perylene bisimide (HDPP‐PBI) was designed and its dimerization behavior was studied. HDPP‐PBI tends to form a quadruple PBI stack with a dimerization constant of ∼5.56×10 6 M −1 . The dimerization was ascribed to synergistic intramolecular double hydrogen‐bonds formation and intermolecular π‐π stacking. Addition of CF3 COOH, a hydrogen bond blocker, promotes the dimer to monomer transition. Accordingly, two distinct fluorescent films were prepared by drop‐casting of the dimerized or the monomeric HDPP‐PBI onto a substrate surface. Interestingly, the less‐emissive PBI quadruple stack‐based film showed a turn on response to acetone vapor, while the highly emissive HDPP‐PBI‐based film exhibited fluorescence quenching upon exposure to triethylamine vapor. We believe that the discovered synergistic effect in the PBI aggregates would enlighten the design of new PAHs aggregates with defined structures. Abstract : A unique "one fluorophore‐two sensing films" is realized based on a typically designed perylene bisimide dimer, HDPP‐PBI, which shows strong tendency to form quadruple PBI aggregate via dimerization in suitable solvents owing to synergistic effect between intramolecular hydrogen bond formation and intermolecular π‐π stacking. Transition from fluorescence silent HDPP‐PBI dimer to fluorescence bright monomer is realized via addition of CF3 COOH.